2014
DOI: 10.1371/journal.pone.0087114
|View full text |Cite
|
Sign up to set email alerts
|

Regional Homogeneity Changes in Hemodialysis Patients with End Stage Renal Disease: In Vivo Resting-State Functional MRI Study

Abstract: ObjectiveTo prospectively investigate and detect early cerebral regional homogeneity (ReHo) changes in neurologically asymptomatic patients with end stage renal disease (ESRD) using in vivo resting-state functional MR imaging (Rs-fMRI).MethodsWe enrolled 20 patients (15 men, 5 women; meanage, 37.1 years; range, 19–49 years) with ESRD and 20 healthy controls (15 men, 5 women; mean age, 38.3 years; range, 28–49 years). The mean duration of hemodialysis for the patient group was 10.7±6.4 monthes. There was no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Results of several previous studies have shown abnormalities in spontaneous brain activity in the DMN regions in patients with ESRD (20)(21)(22). However, the effect of the specific dialysis modality on the DMN in patients with ESRD has not been assessed to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of several previous studies have shown abnormalities in spontaneous brain activity in the DMN regions in patients with ESRD (20)(21)(22). However, the effect of the specific dialysis modality on the DMN in patients with ESRD has not been assessed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum urea, creatinine, and lowered hemoglobin levels affect spontaneous brain activity in patients with ESRD. (20)(21)(22) have been performed in patients with ESRD. Authors of these studies did not investigate the effect of the specific dialysis modality on spontaneous brain activity in patients with ESRD, because they included patients undergoing hemodialysis and PD and those not undergoing dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…There were 46 studies meeting the inclusion criteria for final analysis [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55]. An overview of the reviewed articles is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The test scores were reported as a continuous variable in their statistical tests. One of the studies, reporting the cognitive scores in the context of detecting early cerebral regional homogeneity changes in neurologically asymptomatic patients, found that none of the 20 patients aged <50 years had an abnormal MMSE [33]. In the remaining 13 studies, the prevalence of cognitive impairment varied from 6.6% [43] to 51% [11] with MMSE as the screening tool and from 16% [46] to 39.7% [20] with 3MS as the screening tool.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, resting-state fMRI (rsfMRI) has attracted more attention as a powerful tool to study brain activity in patients at resting state (Snyder and Raichle 2012). To our knowledge, only a few studies on neuropathological mechanism of cognitive impairment in patients with ESRD were carried out by using rs-fMRI (Liang et al 2013;Li et al 2014;Ni et al 2014). Liang et al found progressively decreased regional homogeneity in the default mode network (DMN), frontal and parietal lobes in patients with ESRD (Liang et al 2013).…”
Section: Introductionmentioning
confidence: 99%